Tet1 Regulates Astrocyte Development and Cognition of Mice Through Modulating GluA1 - Xu, Weize; Zhang, Xicheng; Liang, Feng; Cao, Yuhang; Li, Ziyi; Qu, Wenzheng; Zhang, Jinyu; Bi, Yanhua; Sun, Chongran; Zhang, Jianmin; Sun, Binggui; Shu, Qiang; et al. (Frontiers in Cell and Developmental Biology, 2021)
Tet (Ten eleven translocation) family proteins-mediated 5-hydroxymethylcytosine (5hmC) is highly enriched in the neuronal system, and is involved in diverse biological processes and diseases. However, the function of 5hmC in astrocyte remains completely unknown. In the present study, we show that Tet1 deficiency alters astrocyte morphology and impairs neuronal function. Specific deletion of Tet1 in astrocyte impairs learning and memory ability of mice. Using 5hmC high-throughput DNA sequencing and RNA sequencing, we present the distribution of 5hmC among genomic features in astrocyte and show that Tet1 deficiency induces differentially hydroxymethylated regions (DhMRs) and alters gene expression. Mechanistically, we found that Tet1 deficiency leads to the abnormal Ca2+ signaling by regulating the expression of GluA1, which can be rescued by ectopic GluA1. Collectively, our findings suggest that Tet1 plays important function in astrocyte physiology by regulating Ca2+ signaling.